PEMILIHAN PEMINATAN DAN LINTAS MINAT OLEH SISWA SMA NEGERI 1 DAN 5 KOTA BUKITTINGGI - belgi renold; Nofrion Nofrion (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to look at the Selection of Specialization and interest of the interest by students in SMA Negeri 1 and 5 in Bukittinggi City. His type of research is classified as a qualitative descriptive the population of this study were curriculum representative, teachers geographers, counseling teachers, and students at SMAN 1 Bukittinggi and SMAN 5 Bukittinggi. Data collection used documentary observations, and interviews, while data analysis used field notes, data reduction, and data presentation. The results of this study are 1) The procedure for selecting interests and cross interest at SMAN 1 Bukittinggi uses a system with learning outcomes and national examination scores whilein junior high school, While for SMAN 5 Bukittinggi it uses several steps such as filling out a questionnaire, psychological test and maintest, instructur from counseling teachers, and results. Student learning and national examination scores during junior high school for cross interest geography was not available in both schools due to already exceeding teacher hour and a lack of teachers to teach, 2) The role of students in the selection of interests and interests in SMAN 1 and SMAN 5 Bukittinggi city according to the fields and interests of each of the students themselves, 3) The role of geography and BK teachers in SMAN 1 Bukittinggi with on student learning outcomes and national examination scores during junior high school, while SMAN 5 Bukittinggi plays a major role in the selection of interests and cross intetrests using four system. Keywords: Interests, specialization, students